The Role of The Sleman SAR Response Unit in the Implementation of Search and Rescue Operations in Sleman Regency - Prasetya, Dhedi; Mahendra, Gerry Katon (Journal of Social and Policy Issues, 2025)
This study analyzes the operational role of the Sleman SAR Standby Unit (USS Sleman) in conducting search and rescue (SAR) operations and identifies the supporting and inhibiting factors that affect its effectiveness within the local disaster management system. Using a qualitative descriptive approach, data were collected through semi-structured interviews and document analysis. Bruce J. Biddle’s (1986) role theory is applied as the analytical framework, focusing on five components: expectations, norms, performance, evaluation, and sanctions, with additional consideration of contextual factors such as regulatory frameworks, disaster risk characteristics, and organizational capacity. The findings show that USS Sleman performs under well-defined institutional expectations and established national SOPs, reinforced by informal team norms such as discipline and trust. As a first responder and initial field coordinator, the unit plays a vital role in early-stage SAR operations and stakeholder coordination. Despite its generally effective performance, the unit faces several challenges, including limited specialized equipment, logistical constraints, and coordination gaps among agencies. This study contributes to the disaster management literature by offering a role-based operational analysis of a local SAR unit, a topic rarely explored in previous research. It underscores the importance of enhancing institutional capacity, improving inter-agency collaboration, and adapting policies to increase SAR responsiveness and strengthen community resilience in high-risk areas.